Phase I/II Study of Hepatic Arterial Infusion of Nab-paclitaxel in Patients With Metastatic Melanoma to the Liver. (November 2018) - Vera-Aguilera, Jesus; Bedikian, Agop Y.; Bassett, Roland L.; Hwu, Wen-Jen; Kim, Kevin B.; Qin, Yong; Cain, Suzanne; Washington, Edwina W.; Davies, Michael A.; Patel, Sunil M.; Homsi, Jade; Papadopoulos, Nicholas E.; et al.
Abstract : Objectives: Hepatic arterial infusion (HAI) of cytotoxic chemotherapy is a strategy to deliver high dose of anticancer therapy to liver metastases that derive their blood supply from the hepatic artery. Metastatic melanoma (MM) has a high incidence of liver metastases, with uveal subtype in particular exhibiting a predilection for liver dissemination. Nanoparticle albumin-bound paclitaxel (nab-paclitaxel) has demonstrated efficacy in MM and first-pass hepatic metabolism. Therefore, we hypothesized that HAI of nab-paclitaxel would deliver an effective dose of drug to the end organ of interest, with minimal systemic exposure. Patient and Methods: We performed a single-institution open-label phase I/II study of HAI of nab-paclitaxel in MM patients with liver metastasis. Patients received treatment every 21 days at 4 different dose levels. The primary objective of the phase I portion of the study was safety and determination of the maximum-tolerated dose. The primary objective of the phase II portion of the study was overall response rate per Response Evaluation Criteria In Solid Tumors (RECIST) 1.0. Results: A total of 30 patients were treated between 2009 and 2013, 16 of whom had uveal melanoma. The maximum-tolerated dose was 220 mg/m 2 and 19 patients were treated at this dose. There was 1 patient (5%) with a partial response at this dose, and 8 patients (42%) with stable disease at this dose. Conclusions: HAI nab-paclitaxel demonstrates rare objective responses in melanoma patients with liver metastases. This treatment should be studied in combination with checkpoint blockade or other novel treatments to enhance meaningful responses but should not be considered effective monotherapy.